David-Panama Railway Project: a review - Berbey-Álvarez, Aránzazu (2025)
This article presents a review of the status of the Panama-David railway project and its connection with Costa Rica. The methodology corresponds to a documentary review o the topic, SWOT analysis of the project, identification of the externalities of the project, analysis of the Paso Canoas train route (connection Costa Rica)-David (Chiriquí)- Panama. The results of these three tools show the need and potential of the project and its link with Central America. Finally, the conclusions are presented.